Fluvial Erosion Process and Field Measurement Techniques: An Overview - Nda, Muhammad; Adnan, Mohd Shalahuddin; Mohd Yussof, Mohd Azlan; Jimoh, Onemayin David (Penerbit UTHM, 2020)
Fluvial erosion is the detachment of soil particles from the riverbank or bed by the action of numerous factors including land use, vegetation geomorphology, soil properties and climate change. There are various techniques currently available for measuring riverbank erosion at broad range spatial and temporal scales. Riverbank erosion measurements are vital in the documentation of riverbank erosion and deposition. Measurement of riverbank erosion could provide several important information that could be used for various functions, especially in river corridor management. Various measuring techniques have been implemented with varying degrees of success. This paper highlights and discusses different methods, emphasising on their operating principle, merits, and demerits as well as their field application. The measuring techniques include erosion pin, survey, erosion painting, photo electronic erosion pin (PEEP), photogrammetry, and lidar technology. The selected methods discussed in this chapter could help researchers and or practitioners in predicting or evaluating riverbank erosion of a given study area.